2017
DOI: 10.1128/mbio.01343-17
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dietary Resistant Starch on the Human Gut Microbiome, Metaproteome, and Metabolome

Abstract: Diet can influence the composition of the human microbiome, and yet relatively few dietary ingredients have been systematically investigated with respect to their impact on the functional potential of the microbiome. Dietary resistant starch (RS) has been shown to have health benefits, but we lack a mechanistic understanding of the metabolic processes that occur in the gut during digestion of RS. Here, we collected samples during a dietary crossover study with diets containing large or small amounts of RS. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
175
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(195 citation statements)
references
References 62 publications
16
175
1
3
Order By: Relevance
“…This interpretation was related to the lowest RS2 usage (53.7%) in Table . Overall, this data also accords with Haenen et al Variation can possibly be associated with different microbiotal community of the inoculum which was previous described in the multiomics data …”
Section: Resultssupporting
confidence: 93%
“…This interpretation was related to the lowest RS2 usage (53.7%) in Table . Overall, this data also accords with Haenen et al Variation can possibly be associated with different microbiotal community of the inoculum which was previous described in the multiomics data …”
Section: Resultssupporting
confidence: 93%
“…Proteins from Ruminococcaceae and Bacteriodiaceae were also increased in response to RS3. In agreement with our findings, previous studies have reported increases of bacteria from families Bifidobacteriaceae [11,12,[31][32][33], Ruminococcaceae [12,13,15,33], Eubacteriaceae [15,33,34], Lachnospiraceae [35] and Bacteriodiaceae [15,32] in response to different sources and forms of RS. Members of these bacterial families have been shown to be capable of metabolizing resistant starches [17,[36][37][38] due to their amylolytic activities [36,38], and many are butyrate producers [39].…”
Section: Discussionsupporting
confidence: 93%
“…RS can alter the taxonomic composition and functions of the gut microbiome; however, mixed and sometimes opposite effects have been reported [11][12][13][14][15]. In one study, an increase of the Bacteroidetes phylum relative to Firmicutes phylum was observed following an RS4-enriched diet and the opposite following an RS2-enriched diet in human individuals with potential metabolic syndrome [15], whereas in another study RS2 and RS4 in the diet resulted in vastly different effects on the composition of the gut microbiota in healthy human subjects [16].…”
Section: Introductionmentioning
confidence: 99%
“…Rapid hydrolysis of gelatinized starch in the upper gut causes large increases in blood glucose, which in combination with other factors can result in poor insulin control of blood sugar levels and obesity. Consumption of potatoes with less digestible starch (socalled resistant starch) would be expected to ameliorate these effects and might also have health benefits by providing substrates for fermentation by the lower gut microbiome (El Kaoutari et al, 2013;Keenan et al, 2015;Maier et al, 2017;Raigond et al, 2015). Microbiome fermentation produces shortchain fatty acids (SCFA) with beneficial effects including maintenance of optimal function of pancreatic beta-cells that produce insulin (Keenan et al, 2015;Pingitore et al, 2017).…”
Section: Introductionmentioning
confidence: 99%